Records of kogiid whales in Namibia, including the first record of the dwarf sperm whale (Kogia sima) - Elwen, S.H.; Gridley, T.; Roux, J-P.; Best, P.B.; Smale, M.J. (Marine biodiversity records, 2013)
Dwarf (Kogia sima) and pygmy (K. breviceps) sperm whales occur in pelagic waters around southern Africa. Here we report the first record of K. sima from Namibia and provide information on the basic morphometrics and diet of that record and of two recent strandings of K. breviceps. All known records (N = 29) of K. breviceps from Namibia are also collated. Eight families of cephalopod were identified in the stomach contents of the K. sima but no fish remains and few crustacean parts were present. Nine and ten families of cephalopod were identified in the stomachs of the two K. breviceps specimens respectively. This report expands the known range of K. sima by more than 1000 km from previous published records in the region. The sparsely populated nature of the Namibian coast and bias of records towards centres of human habitation suggest Kogia strandings are under reported. The low number of stranded specimens of K. sima from Namibia and west South Africa, in comparison to K. breviceps suggests that K. sima occur rarely or at very low densities in the area influenced by the Benguela current ecosystem. Specimens from Namibia are valuable due to uncertainties about taxomony of kogiids in the region.